IDENTIFIKASI PENGETAHUAN PERAWAT RUANG INTENSIF TENTANG PERAWATAN BERFOKUS PADA PASIEN - Nelfia, Efi "; Dewi, Wan Nishfa; ", Jumaini " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2017)
Abstract The purpose of this research is to identify the knowledge of nurses about patient centred care in intensive care. This research uses a simple descriptive research design. The research was  nurses in intensive care at RSUD Arifin Achmad. Participants involved in the study was nurses who working in intensive care unit a total sample of 75 people with  total sampling technique appropriate inclusion criteria. Research instrument used was  a questionnaire that has been tested for its validity and reliability. Data  analysis used univariate analysis in the frequency distribution. The results showed that the knowledge of nurses on patient  centred was in  medium category which  was 65 people (86.7%) and knowledge of nurses with high category was 10 people (13.5%). Based on the results of this research, hospital institution needs to provide training to nurses about patient-centred  care to improve the performance in providing services to patients Keywords: knowledge, patient centred care